MENDIDIK UNTUK KEHIDUPAN BERDASARKAN KOMPETENSI GURU KRISTEN DI INDONESIA (EDUCATION FOR LIFE BASED ON CHRISTIAN TEACHER COMPETENCE IN INDONESIA) - Edym Bahapol; Youke Singal (Widya Agape School of Theology and Indonesia Christian Theologians Association, 2020)
High quality education is very important for the progress of a society or nation. John Fitgerald Kennedy, former President of the USA 1961-1963, said